Alternative Approaches and Tools for the Transformation of Streetscapes; Direct Physical Interventions and Different Modes of Participation - Kaja Pogačar; Peter Šenk (Prostor, 2018)
The paper presents an overview of a broad range of approaches and tools leading to the substantial spatial and functional transformation of the city streets with the aim to improve the quality of life in urban environments. The approaches range from the traditional top-down planning to the more recent contemporary, informal, creative and adaptive bottom-up approaches involving direct physical interventions and participation of citizens.